Hyperplastic syndrome reproductive system in perimenopausal women: the tactics of conservative therapy and reabilitation - M A Zvychayny (Гинекология, 2014)
The article presents the results of the survey and observation for 3 years 93 women 44-49 years old with hyperplastic processes of the reproductive system: a combination of uterine fibroids (1 to 6 knots, the average size of myoma catch 3,4±1,46 cm) with adenomyosis 1-2nd degree (47 surveyed) and (or) with cystic mastopathy fibozno (84 patients) and 4 -stage receiving complex treatment and rehabilitation, including the use of progestogens on the zero point for the purpose of determining the response of fibroids to therapy, and further x depending on the response to the reception antigestagens.